2022
DOI: 10.3389/fped.2022.901888
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-Mediated Leukocyte Cell-Derived Chemotaxin 2 Is Associated With Liver Fibrosis in Biliary Atresia

Abstract: ObjectiveBiliary atresia (BA) presents as a severe infantile cholangiopathy disease, characterized by progressive liver fibrosis and the resulting poor prognosis. Leukocyte cell-derived chemotaxin 2 (LECT2) was proposed as the key gene associated with hepatic fibrosis in BA, but the molecular mechanism is unclear. This study aims to investigate the function of LECT2 in BA.MethodsA total of 53 patients were enrolled in this study; 36 patients with BA, and 17 control patients with cholestasis, including congenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Another study found that LECT2 was also highly expressed in the sera of children with BA. 102 Dong et al . 103 used miRNA microarray analysis to screen differentially expressed microRNAs (miRNAs) in the sera of patients with BA and those with non-BA neonatal cholestasis.…”
Section: Other Potential Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study found that LECT2 was also highly expressed in the sera of children with BA. 102 Dong et al . 103 used miRNA microarray analysis to screen differentially expressed microRNAs (miRNAs) in the sera of patients with BA and those with non-BA neonatal cholestasis.…”
Section: Other Potential Biomarkersmentioning
confidence: 99%
“…Another study found that LECT2 was also highly expressed in the sera of children with BA. 102 Dong et al 103 used miRNA microarray analysis to screen differentially expressed micro-RNAs (miRNAs) in the sera of patients with BA and those with non-BA neonatal cholestasis. They found that the expression levels of miR-4429 were significantly downregulated whereas those of miR-4689 were significantly upregulated in the sera of patients with BA, suggesting that miR-4429 and miR-4689 could serve as potential diagnostic biomarkers of BA.…”
Section: Other Potential Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of diseases is also a hot research direction of LECT2, especially for tumors like HCC and breast cancer (13,40,47,48). BA is the fifth research hotspot to study the mechanism of LECT2-induced liver fibrosis in patients with Biliary Atresia (49). We drew a mechanism diagram by Figdraw to illustrate how LECT2 affects the development of related diseases, including HCC, liver fibrogenesis, bacterial sepsis, inflammatory response (Figure 9).…”
Section: Research Hotspots and Frontiersmentioning
confidence: 99%
“…It has been shown that LECT2 levels were 31.2 (20.9, 41.5) ng/mL in the group of people with NAFLD compared to those without NAFLD, which was significantly higher than in the group without NAFLD ( 37 ). It is proposed that LECT2 is highly expressed in both hepatic tissue and serum in biliary atresia (BA), suggesting that LECT2 can be used as a biomarker for BA ( 38 ). LECT2 levels are increased in patients with metabolic syndrome (MetS) and correlate with severity, suggesting that LECT2 can be used as a biomarker for MetS ( 39 ).…”
Section: Diagnostic Indicatorsmentioning
confidence: 99%